Konstruksi Sosial Masyarakat Tentang Kearifan Lokal di Era Perkembangan Iptek (Studi Fenomenologi Di Kota Tegal) - Mursyidah Dwi Hartati; Tity Kusrina (Universitas Pancasakti Tegal, 2019)
The social transformation of Tegal society has brought a logical consequence to the society, economically, culturally and politically. Local wisdom provides public protection to survive in the midst of social change. The ability of the Tegal community in dealing with social change is one of the determinants of social wisdom that is there. Some of the things that prove to be the impact of globalization and the advancement of IPTEK in Tegal include; (i) the entry of Hand Phone and (ii) influence in transportation. Efforts to strengthen the nation's identity and maintain the local wisdom of the people of Tegal have had enough awareness and it was built through a small scope such as family, village, village, town. Villagers usually have more and more resistance to the threat of change. The aspect of the change referred to here is the trasisi of the agrarian society towards the industrial community. Certainly it is a consequence, but researchers have identified some social wisdom that characterized the people of Tegal